DEMAND ELASTICITY IN TRANSPORT AND ELASTICITY OF AVERAGE EMPLOYEE WAGES (Perner's Contacts, 2009)
Income elasticity measures extent of demand change in dependence on changes of customers income. It is important tool of transport economist for analysis of transport demand. Regression a correlation analysis can be used by examination of relation between income (wages of employees) and demand for public transport, next calculation of elasticity coefficients will be made as well.
Keywords: demand elasticity; income; public transport